Development of Learning Media Using Smart Apps Creator Based on Problem Based Learning for Social Science Learning in Grade IV of Elementary School - Raidha Elsa Aprilianti; Yeni Erita (STKIP Taman Siswa Bima, 2025)
This study aims to develop a learning media using Smart Apps Creator with a PBL approach that is valid, practical, and effective. The method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The designed media was validated by subject matter experts, language experts, and media experts, and was also tested for its practicality and effectiveness through questionnaires and learning outcome tests. The findings indicate that the learning media is valid, practical, and effective for use in the teaching and learning process. The validation score from the three validators reached 91%, categorized as